Market institutions and price relationships: The case of coffee in the Ethiopian Commodity Exchange - Hernandez, Manuel A.; Rashid, Shahidur; Lemma, Solomon; Kuma, Tadesse (Wiley, 2017)
While the Ethiopian Commodity Exchange (ECX) is widely considered a successful market institution, very little rigorous empirical investigation has been done on it. This paper contributes to filling this knowledge gap. Using a unique set of spatially disaggregated prices for five different coffee varieties, we examine how the ECX has influenced the dynamics of international and domestic prices for coffee, the largest traded commodity in terms of trade value on the exchange floor. We follow a multivariate Generalized Autoregressive Conditional Heteroscedasticity (GARCH) approach to assess the extent of market interdependence (conditional correlations) and volatility transmission. We also evaluate structural changes in price dynamics over time. Our results suggest that, contrary to popular media stories, the ECX's success in strengthening coffee price relationships has been limited. We discuss the underlying reasons and implications of this finding.